2005
DOI: 10.1081/ese-200046614
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Recovery of Phosphorus from Waste-Activated Sludge Incinerator Ash

Abstract: Several batch studies that were made up of the acid extraction and the solvent extraction were performed to recover phosphorus from the waste-activated sludge (WAS) incinerator ash. In the acid extraction, the extraction efficiency of phosphorus relied on the acid type, liquid(acid)-to-solid (L(acid)S) ratio, and acid concentration. Phosphorus in the WAS incinerator ash was completely extracted by 1 M HCl at the L(acid)S ratio of 6.4:1. Subsequently, the solvent extraction was conducted to separate and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 12 publications
1
29
0
1
Order By: Relevance
“…Apart from liquid waste, ash from municipal sewage sludge generated by incineration is P-rich and has potential for struvite recovery (P constitutes 13-25% of the total mass) (Hong et al, 2005;Xu et al, 2012). However, it requires mechanical, thermal (incineration) or chemical (acid/base leach) pre-treatments to allow for P recovery because of its strong retention with other elements like Ca, Mg, Al and Fe (Hong et al, 2005).…”
Section: Municipal Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Apart from liquid waste, ash from municipal sewage sludge generated by incineration is P-rich and has potential for struvite recovery (P constitutes 13-25% of the total mass) (Hong et al, 2005;Xu et al, 2012). However, it requires mechanical, thermal (incineration) or chemical (acid/base leach) pre-treatments to allow for P recovery because of its strong retention with other elements like Ca, Mg, Al and Fe (Hong et al, 2005).…”
Section: Municipal Wastementioning
confidence: 99%
“…However, it requires mechanical, thermal (incineration) or chemical (acid/base leach) pre-treatments to allow for P recovery because of its strong retention with other elements like Ca, Mg, Al and Fe (Hong et al, 2005).…”
Section: Municipal Wastementioning
confidence: 99%
“…For example, Takahashi et al [17] have found that phosphorus and various heavy metals in the incinerated wastewater treatment sludge can be extracted when the pH of the ash fell below 2.0 by adding sulfuric acid. Hong et al [10] revealed that phosphorus in the waste-activated sludge incinerator ash was completely extracted by 1 M HCl at the L acid S ratio of 6.4:1. Liao et al [18,19] have reported that by using microwave treatment for only 5 min, about 80% of total phosphorus in the sewage sludge could be released into solution.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies on P recovery technologies by the application of the solvent-extraction method have attracted considerable attention [10]. However, these methods not only use a large amount of organic solvent such as butyl-alcohol or tri-butyl phosphate to extract P but also require a very complicated procedure.…”
Section: Yearsmentioning
confidence: 99%
“…Another process for phosphorus recovery involving dissolution of ash from sewage sludge in acid using ion exchange and recovering the phosphorus in the form of phosphoric acid has been suggested by Jensen (2000). Hong et al (2005) describe how phosphoric acid can be extracted with organic solvents after dissolution of incinerated sewage sludge ash with sulphuric or hydrochloric acid. Another process is based on heating the ash up to 1,400 o C to vaporise elemental phosphorus, which is condensed in water and oxidised to phosphoric acid (Japanese patent 9145038, 1997).…”
Section: Phosphorus Recovery From Sewage Sludge Ashmentioning
confidence: 99%